Influence of ionizing radiation on the performance of MIS solar cells: A theoretical model - Chauhan R.K.; Chakrabarti P. (My University, 2025)
A theoretical model of a metal-insulator-semiconductor (MIS) solar cell has been developed to investigate the effect of ionizing radiation on device characteristics (AMO) such as the open-circuit voltage, the short-circuit current, the fill factor, and the efficiency in the post-irradiated condition. The model takes into account the effects of ionizing radiation-induced oxide and interface trapped charges of a MIS structure to examine its characteristics in the post-irradiated condition. The I-V characteristics of the solar cell degrade considerably in the post-irradiated condition, depending on the total dose received by the device. The post-irradiated efficiency of the device falls significantly, making the device unattractive for application in a radiation environment. The results of the study are expected to be useful in predicting the total life of MIS solar cells in a hostile environment where they are exposed to a variety of ionizing radiation.